Peak systolic to end diastolic flow velocity ratio is associated with ductal patency in infants below 32 weeks of gestation. Issue 2 (18th November 2014) - Smith, A; Maguire, M; Livingstone, V; Dempsey, E M
Abstract : Background: Early diagnosis and effective treatment of the patent ductus arteriosus (PDA) in infants less than 32 weeks gestation remains contentious. Objective: To determine which clinical and echocardiographic parameters are associated with PDA patency in preterm infants less than 32 weeks gestation. Design/Methods: This was a prospective cohort study. An echocardiography (echo) was performed within 12–48 h of birth and a follow-up echo at 1 month of life. Parental consent was obtained. Results: 55 babies were enrolled. Median (range) gestation was 28 (24–31) weeks and birth weight 1090 g (470–1800 g). ECHO 1 demonstrated that 50 babies had a PDA present within 48 h of birth, of which 19 were large (≥2 mm) (36%) and 31 were small (59%) on colour Doppler assessment of duct diameter. Three babies died before 1 month. At 1 month 30 babies still had a PDA (58%), 10 of which were large (19%) and 19 were small (36%). Parameters significantly associated with large PDAs versus no PDA at 1 month were gestational age (26 weeks vs 30 weeks, p=0.002), birth weight (860 g vs 1290 g, p=0.007) and ventilator support at 48 h (80% vs 17%, p=0.001). Echo parameters revealed that ductal size on colour Doppler (2.5 mm vs 1.5 mm, p=0.003), end diastolic flow velocity (57 m/s vs 147 m/s, p<0.001) and peak systolic to end diastolic flow velocity ratio (2.29 vs 1.23, p=0.001) at 48 h were associated with large PDAs at 1 month. Conclusions: For infants less than 32 weeks gestation a peak systolic to end diastolic flow velocity ratio>2 within 48 h of birth is associated with a persistent large PDA at 1 month of age.